Chronic Arsenic Exposure through Drinking Water and Risk of Type 2 Diabetes Mellitus: A Study from Bangladesh - Nesha, Mst Karimon; Islam, Md Nazrul; Ferdous, Nira; Nazrul, Fahid Bin; Rasker, Johannes J (Journal of Bangladesh College of Physicians and Surgeons, 2018)
The well-documented fact that chronic arsenic exposure can lead to skin lesions, atherosclerotic diseases and cancers. The findings of association between arsenic exposure and diabetes mellitus indicate additional risk to human health. The aim of this study was to observe the association of chronic arsenic exposure from drinking water and risk of development of type 2 diabetes mellitus. To this end, a cross-sectional study was conducted in Comilla district of Bangladesh where ground water is heavily contaminated with arsenic. The individuals unexposed to arsenic were recruited from the Jhenaidah district. People with arsenic-related skin lesions were defined as subjects exposed to arsenic. Diabetes was defined if fasting blood glucose (FBG)>6.1 mmol/L following World Health Organization (WHO) guidelines. The common odds ratio for diabetes mellitus among subjects exposed to arsenic was 3.5 (95% confidence interval 1.1-10.9). After adjustment for age, sex and BMI, the Mantel-Haenszel weighted prevalence ratio was 3.5 (95% CI: 1.1-11.1); 3.7 (95% CI: 1.1-11.8) and 4.4 (95% CI: 1.1-17.2) respectively. The indicated relationships were significant (P<0.05). The observations suggested, chronic arsenic exposure through drinking water may be a risk factor of type 2 diabetes mellitus. J Bangladesh Coll Phys Surg 2019; 37(1): 5-12